PROPERTY DAMAGE AS A DERIVATIVE CONSEQUENCE OF INTENTIONAL DESTRUCTION OR DAMAGE OF HOUSING AND COMMUNAL OBJECTS (Bulletin of criminological association of Ukraine, 2024)
The work is devoted to the study of socially dangerous consequences of intentional destruction or damage to housing and communal facilities (Article 270-1 of the Criminal Code of Ukraine). The presence of a whole series of socially dangerous consequences was established as a mandatory feature of the objective side of the analyzed crime, the main ones - destruction or damage of housing and communal facilities, intermediate ones - impossibility of operation or violation of the normal functioning of such objects, derivatives - danger to life or health of people or property damage in a large amount. Emphasis is placed on the impossibility of identification in Art. 270-1 of the Criminal Code of Ukraine of socially dangerous consequences in the form of destruction or damage to property with socially dangerous actions. It is through the prism of socially dangerous consequences that the categories of destruction and damage can be distinguished, since the same actions in some conditions can cause the destruction of certain property, and in others - only its damage. Thus, the destruction or damage of property is the main socially dangerous consequence of the composition of the criminal offense provided for in Art. 270 of the Criminal Code of Ukraine. Derivative consequences in the form of property damage of a certain size are the main distinguishing feature of criminal destruction of housing and communal facilities from non-criminal ones. It has been proven that the calculation of property damage as a result of damage or destruction of an object of housing and communal services, in contrast to the theft of property, is carried out taking into account not only the value of this or that property or its part, but also the costs necessary to restore the operation of the corresponding object of law property
Keywords: crime; destruction; damage; housing and communal facilities; socially dangerous consequences; large property damage